2014
DOI: 10.1681/asn.2013050481
|View full text |Cite
|
Sign up to set email alerts
|

The Regenerative Potential of Parietal Epithelial Cells in Adult Mice

Abstract: Previously, we showed that some podocytes in juvenile mice are recruited from cells lining Bowman's capsule, suggesting that parietal epithelial cells (PECs) are a progenitor cell population for podocytes. To investigate whether PECs also replenish podocytes in adult mice, PECs were genetically labeled in an irreversible fashion in 5-week-old mice. No significant increase in labeled podocytes was observed, even after 18 months. To accelerate a potential regenerative mechanism, progressive glomerular hypertroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 46 publications
5
88
0
Order By: Relevance
“…We therefore examined the UNx model in which we could not detect, at least in our experimental set-up, any podocyte turnover, a finding that confirms the work of others. 28 These results confirm that glomerular and podocyte hypertrophy is the main adaptation mechanism, which is in line with previous reports. 23,29 Although signaling pathways such as mammalian target of rapamycin that efficiently increase podocyte size have been identified, 5,30,31 the lack of podocyte turnover in response to nephron loss makes these enlarged podocytes the obvious Achilles heel in progressive kidney diseases.…”
Section: Discussionsupporting
confidence: 93%
“…We therefore examined the UNx model in which we could not detect, at least in our experimental set-up, any podocyte turnover, a finding that confirms the work of others. 28 These results confirm that glomerular and podocyte hypertrophy is the main adaptation mechanism, which is in line with previous reports. 23,29 Although signaling pathways such as mammalian target of rapamycin that efficiently increase podocyte size have been identified, 5,30,31 the lack of podocyte turnover in response to nephron loss makes these enlarged podocytes the obvious Achilles heel in progressive kidney diseases.…”
Section: Discussionsupporting
confidence: 93%
“…59,65 Wanner et al 66 recently showed that podocyte generation is mainly active during glomerular development and may occur after acute glomerular injury but was not observed in aging kidneys or in response to nephron loss. Interestingly, a recent study by Berger et al 67 showed that parietal podocytes (PECs expressing podocyte markers) disappeared from Bowman's capsule as glomeruli gradually underwent physiologic hypertrophy, suggesting that there is a functional podocyte reserve that directly differentiates into podocytes on Bowman's capsule. Berger et al 68 proposed that this is explained by the lack of space to accommodate podocytes on the small glomerular tuft of a young child.…”
Section: Discussionmentioning
confidence: 99%
“…Stress and loss of podocytes is likely one of the major determinants of progressive glomerular injury and glomerulosclerosis given their unique anatomical position and terminal differentiation with virtually no regenerative capability (98,99). Pathways contributing to podocyte injury and glomerulosclerosis (100) amongst others include the epidermal growth factor receptor (EGFR) (90), mTOR (101)(102)(103), angiotensin II (104), miR-193a (105), KLF-4 (106), adiponectin (107), RAP1GAP (82), or Rho-A (108).…”
Section: The Role Of Glomerular Cellsmentioning
confidence: 99%